Rheological Properties of Bitumen Containing Organic Foaming Agent for Warm Mix Asphalt - MOHD HELMI, NUR HAZWANI (Universiti Teknologi PETRONAS, 2018)
“The environmental friendly surrounding is important for living thing around the world. Construction of roads contributes a lot of emission of greenhouse gases to global warming. The construction of roads usually use Hot Mix Asphalt (HMA) technologies which need to heat at temperature 160 ̊C and consume more energy which lead to environmental pollution. Therefore, Warm Mix Asphalt (WMA) technology is a practical solution for environment because the bitumen mix, lay and compact at temperatures 20 ̊C to 40 ̊C lower than Hot Mix Asphalt (HMA). The reduction of WMA temperature involves the use of organic additives, chemical additives and water based foaming process are to facilitate mixing, laying and compaction. Thus, their main aim is to reduce the viscosity of bitumen, which improves workability, produces less emission and lead to better working condition.